2013
DOI: 10.1111/1468-5973.12011
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Performativity to Crisis Management Theory: An Illustration from the 2003 French Heat Wave Crisis Response

Abstract: International audienceWhile current crisis management literature focuses on the necessity of consistent data and shared interpretation to coordinate effectively, contrastingly, this paper highlights the predominating influence of crisis responders' performances on information transmission. Based on an exploratory interpretive analysis of the 2003 French heat wave crisis response, our findings reveal that performances can support immediate reaction and involvement, but can also generate conflicts or misundersta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Sensemaking is a particularly promising theoretical framework for disaster response management, as it acknowledges explicitly that individuals interpret ongoing events not in a 'right' or 'wrong' way but develop individually plausible interpretations based on their respective situation, which explains why interpretations of events diverge substantially between individuals, groups and organizations at a given point in time (Weick, 1993;Weick, Sutcliffe & Obstfeld, 2005). Considering sensemaking as the link between cognition and action, we can derive a clearer understanding of the cognitive and affective underpinnings of multiagency coordination, as some studies demonstrated (e.g., Adrot et al, 2013;Linnenluecke et al, 2013;Schraagen et al, 2011). Employing these and other conceptually well-rooted theories could be the next step towards a theory of disaster response management, which is currently only vaguely visible on the horizon.…”
Section: Research Agendamentioning
confidence: 95%
See 1 more Smart Citation
“…Sensemaking is a particularly promising theoretical framework for disaster response management, as it acknowledges explicitly that individuals interpret ongoing events not in a 'right' or 'wrong' way but develop individually plausible interpretations based on their respective situation, which explains why interpretations of events diverge substantially between individuals, groups and organizations at a given point in time (Weick, 1993;Weick, Sutcliffe & Obstfeld, 2005). Considering sensemaking as the link between cognition and action, we can derive a clearer understanding of the cognitive and affective underpinnings of multiagency coordination, as some studies demonstrated (e.g., Adrot et al, 2013;Linnenluecke et al, 2013;Schraagen et al, 2011). Employing these and other conceptually well-rooted theories could be the next step towards a theory of disaster response management, which is currently only vaguely visible on the horizon.…”
Section: Research Agendamentioning
confidence: 95%
“…This in turn limits the consequences of a lack of trust and helps to contain the adverse effects of impression management. A strong vertical hierarchy might also mitigate this problem (Adrot & Moriceau, 2013;Kapucu, 2006), but both strong centralization and decentralization come at a price (cf. below).…”
Section: Communicationmentioning
confidence: 99%
“…During and after the July 22, 2011, terrorist attack in Norway, for instance, the Prime Minister effectively communicated the grief and patriotism of the nation, but the Minister of Justice came to be negatively perceived as an apologist for the police (Christensen, Lægreid, & Rykkja, 2013). The dramaturgy of crisis requires crisis leaders to appreciate that strategic action is simultaneously instrumental and performative (Adrot & Moriceau, 2013; ‘t Hart, 1993).…”
Section: Introduction: the Challenges Of Strategic Crisis Managementmentioning
confidence: 99%
“…This serves to obfuscate the differences and reduces the potential for developing a notion of sensemaking that does not rely on purely cognitive thought processes. Nonetheless, Adrot and Moriceau (2013) offer an interesting comment on performance and sensemaking when argue that while words provide a certain number of cues, performativity (i.e., performing an enacting sense) transmits 'not only informational or cognitive, but also emotional, affective, embodied and situated' sense (p. 28).…”
Section: The Challenges and Promises Of Using Csmmentioning
confidence: 99%